Raman spectroscopic study for the determination of monoethanolamine concentration - Wong, M.K. (Trans Tech Publications Ltd, 2014)
Thermodynamic model is one of the important elements in designing and operating CO2 removal systems, thus accurate determination of the thermodynamic properties of CO2 in aqueous amine is of major interest for both technical and economical considerations. Quantitative Raman study of aqueous monoethanolamine (MEA) solutions of concentration ranging from 0 to 99 mass in the spectral region between 300 and 3100 cmâ 1 was performed. Band envelopes were resolved with Gaussian Lorentzian function. Progressive growth of area under these peaks with increasing concentration was used as the parameter to construct calibration curve. Area ratio of selected peaks was plotted against MEA concentration to depict the relationship between MEA concentration and each area ratio. Correlation for A1460/A933 has coefficient of determination closest to unity and lowest mean squared area. MEA concentration can be calculated from the equation derived from correlation between A1460/A933 and MEA mass . Â© 2014 Trans Tech Publications, Switzerland.